Salt Tolerance of Maize and Sorghum Genotypes - Totawat, K L; Mehta, A K (Annals of Arid Zone, 2016)
Irrigation water of higher salinity levels led to significant decrease in dry matter yield, leaf area, height and nutrient uptake of maize and sorghum genotypes The maize genotypes Ganga-5 and Ganga-2 and sorghum genotypes CHS-5 recorded significantly higher leaf area, heighr, dry matter yield and nutrient uptake. These genotypes showed high Na/K ratio too.